Self-Regulation, Learning Problems, and Maternal Authoritarian Parenting in Chinese Children: A Developmental Cascades Model. - Liu, Junsheng; Xiao, Bowen; Hipson, Will E.; Coplan, Robert J.; Yang, Panpan; Cheah, Charissa S. L. (Journal of Child & Family Studies, 2018)
The ability to intentionally control behavior to achieve specific goals helps children concentrate in school and behave appropriately in social situations. In Chinese culture, where self-regulation is highly valued by parents and teachers, children’s difficulties self-regulating may contribute to increased learning problems and subsequent authoritarian parenting. In this study we explored the longitudinal linkages among Chinese children’s self-regulation, learning problems, and authoritarian parenting using a developmental cascades model. Participants were N = 617 primary school students in Shanghai, P.R. China followed over three years from Grade 3-4 to Grade 5-6. Measures of children’s self-regulation, learning problems, and maternal authoritarian parenting were obtained each year from a combination of child self-reports and maternal and teacher ratings. Among the results: (1) compared with the unidirectional and bidirectional models, the developmental cascades model was deemed the best fit for the data; (2) earlier self-regulation negatively predicted later authoritarian parenting via a pathway through academic performance; (3) academic performance directly and indirectly contributed to greater self-regulation. Results are discussed in terms of the implications of self-regulation for Chinese children’s academic success and authoritarian parenting practices.